IgA vasculitis (Henoch-Schonlein purpura) in children: A Kashmir experience - Mohd Ashraf; Anisa Riyaz; Sayar Ahmed Bhat; Khurshid Ahmed Wani; Naseer Yousuf Mir; Syed Ashiq Nisar Andrabi; Asma Wani (Al Ameen Medical College, 2021)
Background: Immunoglobulin A vasculitis (IgAV) also known as Henoch-Schonlein purpura is a common form of primary vasculitis, characterized clinically by palpable skin rash and one or more gastrointestinal, musculoskeletal, and/or renal system(s) involvement. It is more common in less than 10 years, with overall good prognosis. Half of the IgAV patients do have kidney involvement, with very small percentage progress to end stage kidney disease (ESKD). Objective: To know the incidence, clinical profile and outcome of IgAV (Henoch-Schonlein purpura) among hospitalized children in Kashmir province. Methods: This retrospective study, analysed the case records of all hospitalized patients between 1-18 years, diagnosed with IgAV over the last three years (April, 2017- March 2020). Data on clinical profile, laboratory abnormalities and outcomes were extracted. Results: Out of 40681 hospitalised children, 40 had IgAV, where 37 (92.5%) were between 3-10 years, with male female ratio of 1.8:1. Skin rash was observed in 38 (95%) children, gastrointestinal (GI) symptoms in 27 (67.5%), musculoskeletal symptoms in 18(45%) children, while as 11 (27.5%) had renal involvement. Two girls each of 6 and 7 years, and one 7-year boy presented as nephrotic syndrome with hematuria, who underwent renal biopsy, received prolonged immunosuppression, and are doing well with preserved renal functions till last follow up. Conclusion: Boys between 3-10 years were the commonest IgAV affected age group, where 95% had skin, 67.5% had GIT, 45% had musculoskeletal and 27.5% children had renal involvement.